A Clinical Study of the Modified Thread Carpal Tunnel Release. (September 2017) - Guo, Danqing; Guo, Danzhu; Guo, Joseph; Schmidt, Steven C.; Lytie, Rachel M.
Background: Previous studies have indicated that the thread carpal tunnel release (TCTR) is a safe and effective technique. Through a study on 11 cadaveric wrists, the TCTR procedure was modified and the needle control accuracy was improved to 0.15 to 0.2 mm, which is precise enough to preserve superficial palmar aponeurosis (SupPA), Berrettini branch, and common digital nerves. The aim of the present study was to verify the modified TCTR clinically.Methods : The modified TCTR was performed on 159 hands of 116 patients. The Boston Carpal Tunnel Syndrome Questionnaire was used for assessing the outcomes. Statistical analyses were used to compare the outcomes with the available data from the literature for the open and endoscopic techniques.Results: TCTR led to significant improvement in the short-term results, and the outcomes were better in long-term results compared with the open or endoscopic release. The SupPA, Berrettini branch, and common digital nerves were protected. There was no neurovascular complication for any case. Significant relief of symptoms was observed 3 to 5 hours post procedure. Most patients used their hands on the day of the procedure for simple daily activity. Patients reported their sleep quality was improved on the surgical day. Most patients with office jobs were able to return to work on postoperative day 1, and those with repetitive jobs returned to work in about 2 weeks. The statistical evidence proves that the modified TCTR procedure results in improved clinical outcomes as compared with open carpal tunnel release (CTR) and endoscopic CTR.Conclusions: The TCTR procedure has been shown to be a safe and effective technique for CTR. The modified TCTR procedure minimizes postoperative complications, such as pillar pain, scar tenderness, or functional weakness, by avoiding unnecessary injuries to the surrounding structures around the transverse carpal ligament during the procedure.